Effect of Drying on Selected Physical Properties of "Asontem" Cowpea Variety. (18th July 2012) - Bart-Plange, Ato; Dzisi, Komla Agbeko; Ampah, Jonathan
Abstract : Storage, handling, processing, and other postharvest operations of agricultural products require information about their physical properties for the design of related machinery. This study was carried out to evaluate the effect of drying on some physical properties of " asontem " cowpea variety within the moisture content range of 19.00% wb and 9.58% wb using standard techniques. Four levels of moisture content were used namely, 19.00%, 15.13%, 11.50%, and 9.58% wb. The average length, width, and thickness decreased with decreasing moisture content from 8.16 to 7.11 mm, 6.36 to 6.28 mm and 4.77 to 4.61 mm respectively. The geometric mean diameter, surface area, and volume decreased nonlinearly with decreasing moisture content from 6.27 to 5.89 mm, 123.88 to 109.46 mm 2, and 130.23 to 108.02 mm 3, respectively. 1000 grain mass decreased non-linearly from 132.85 to 120.92 g and true density increased non-linearly with decreasing moisture content from 1063.80 to 1185.92 kg/m 3 . The filling angle of repose decreased non-linearly from 29.34 to 27.92°, while the coefficient of static friction also decreased non-linearly from 0.36 to 0.29, 0.35 to 0.28, and 0.31 to 0.21 for plywood, mild steel, and rubber, respectively.